Roles of TRPV1 and TRPA1 in Spontaneous Pain from Inflamed Masseter Muscle. (1st August 2018) - Wang, Sheng; Brigoli, Benjamin; Lim, Jongseuk; Karley, Alisha; Chung, Man-Kyo
Highlights: Inhibition of TRPA1 attenuated mouse grimace scale during muscle inflammation but not face wiping. Scavenging putative ligands for TRPV1 or TRPA1 attenuated mouse grimace scale scores. Simultaneous inhibition of TRPV1 and TRPA1 additively produced conditioned place preference. Simultaneous inhibition of TRPV1 and TRPA1 did not affect bite-evoked pain. Abstract: Craniofacial muscle pain, such as spontaneous pain and bite-evoked pain, are major symptoms in patients with temporomandibular disorders and infection. However, the underlying mechanisms of muscle pain, especially mechanisms of highly prevalent spontaneous pain, are poorly understood. Recently, we reported that transient receptor potential vanilloid 1 (TRPV1) contributes to spontaneous pain but only marginally contributes to bite-evoked pain during masseter inflammation. Here, we investigated the role of transient receptor potential ankyrin 1 (TRPA1) in spontaneous and bite-evoked pain during masseter inflammation, and dissected the relative contributions of TRPA1 and TRPV1. Masseter inflammation increased mouse grimace scale (MGS) scores and face wiping behaviors. Pharmacological or genetic inhibition of TRPA1 significantly attenuated MGS but not face wiping behaviors. MGS scores were also attenuated by scavenging putative endogenous ligands for TRPV1 or TRPA1. Simultaneous inhibition of TRPA1 by AP18 and TRPV1 by AMG9810 in masseter muscle resulted in robust inhibition of both MGS and face wiping behaviors. Administration of AP18 or AMG9810 to masseter muscle induced conditioned place preference (CPP). The extent of CPP following simultaneous administration of AP18 and AMG9810 was greater than that induced by the individual antagonists. In contrast, inflammation-induced reduction of bite force was not affected by the inhibition of TRPA1 alone or in combination with TRPV1. These results suggest that simultaneous inhibition of TRPV1 and TRPA1 produces additive relief of spontaneous pain, but does not ameliorate bite-evoked pain during masseter inflammation. Our results provide further evidence that distinct mechanisms underlie spontaneous and bite-evoked pain from inflamed masseter muscle.